2022
DOI: 10.1136/bmjopen-2021-058495
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the price elasticity of demand for waterpipe and cigarette smoking in Lebanon, Jordan and Palestine: a volumetric choice experiment

Abstract: ObjectivesThis study assessed the extent to which the elasticity of cigarette and waterpipe tobacco products differs between men and women. We also explored the levels of substitution and complementarity in tobacco products among men and women.SettingThe study examines tobacco elasticities in three Arab countries: Lebanon, Jordan and the West Bank of Palestine.ParticipantsWe used data from nationally representative surveys of adults aged ≥18 years in Lebanon (n=1680), Jordan (n=1925) and Palestine (n=1679). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…That is, males in Jordan have a higher probability to smoke, compared to females. This can be attributed to sociocultural approval which accepts male smoking more than female smoking [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, males in Jordan have a higher probability to smoke, compared to females. This can be attributed to sociocultural approval which accepts male smoking more than female smoking [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study established in Jordan and the West Bank of Palestine has demonstrated the importance of taxes in reducing the prevalence of tobacco products and the economic burden associated with it. The fact that people usually substitute different tobacco products such as conventional cigarettes, water-pipes, and e-cigarettes shows the importance of applying taxes on all tobacco products, not only on certain products [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding price elasticity by gender is limited. Some studies conclude that women are more sensitive to price changes than men, particularly among younger age groups [25][26][27]. However, other studies suggest that men have a higher price elasticity in tobacco consumption [28,29].…”
Section: Plos Onementioning
confidence: 99%
“…It does this by simultaneously offering multiple distinct volumetric choices across competing products. Data from Jordan, Palestine, and Lebanon show the elasticity of demand for waterpipe tobacco products and the existence of substitution between tobacco products, which should be considered when formulating tobacco taxation strategies [ 42 ]. Thus, VCEs allow for the estimation of a complete set of own-price and cross-price elasticities that are instrumental for the purpose of fiscal policy simulations [ 3 ].…”
Section: Vces For Tobacco Control Researchmentioning
confidence: 99%